2020
DOI: 10.3389/fcell.2020.616139
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Mitochondrial Quality Control by Natural Drugs in the Treatment of Cardiovascular Diseases: Potential and Advantages

Abstract: Mitochondria are double-membraned cellular organelles that provide the required energy and metabolic intermediates to cardiomyocytes. Mitochondrial respiratory chain defects, structure abnormalities, and DNA mutations can affect the normal function of cardiomyocytes, causing an imbalance in intracellular calcium ion homeostasis, production of reactive oxygen species, and apoptosis. Mitochondrial quality control (MQC) is an important process that maintains mitochondrial homeostasis in cardiomyocytes and involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 202 publications
(167 reference statements)
0
32
0
Order By: Relevance
“…Mitochondrial dysfunction is an important contributor to the pathogenesis of myocardial stress, together with oxidative stress, protein misfolding, and inactive protein denaturation ( Zhou et al, 2017a ; Kobayashi et al, 2020 ; Ma et al, 2020b ; Wang et al, 2020b , c ). The accumulation of reactive oxygen species promotes the mutation of mitochondrial DNA ( Wang et al, 2019a ; Chang et al, 2020 ; Szaraz et al, 2020 ), while the disruption of the tricarboxylic acid cycle depletes the cellular energy supply and accelerates cellular aging ( Cao et al, 2019 ; Mukwaya et al, 2019 ). Myocardial stress can lead to myocardial cardiac ischemia, myocardial infarction, hyperglycemia-induced myocardial damage, and pressure load-induced myocardial injury ( Zhou et al, 2019a ; Ajoolabady et al, 2020 ; Jusic and Devaux, 2020 ; Santin et al, 2020 ; Wang et al, 2020g ; Zhou et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction is an important contributor to the pathogenesis of myocardial stress, together with oxidative stress, protein misfolding, and inactive protein denaturation ( Zhou et al, 2017a ; Kobayashi et al, 2020 ; Ma et al, 2020b ; Wang et al, 2020b , c ). The accumulation of reactive oxygen species promotes the mutation of mitochondrial DNA ( Wang et al, 2019a ; Chang et al, 2020 ; Szaraz et al, 2020 ), while the disruption of the tricarboxylic acid cycle depletes the cellular energy supply and accelerates cellular aging ( Cao et al, 2019 ; Mukwaya et al, 2019 ). Myocardial stress can lead to myocardial cardiac ischemia, myocardial infarction, hyperglycemia-induced myocardial damage, and pressure load-induced myocardial injury ( Zhou et al, 2019a ; Ajoolabady et al, 2020 ; Jusic and Devaux, 2020 ; Santin et al, 2020 ; Wang et al, 2020g ; Zhou et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that these drugs have the pharmacological effects of antioxidative stress and regulating MQC. In the process of high-lipid, high-glucose, or anoxia-induced redox imbalance or mitochondrial dysfunction, it can have a good protective effect on cells [ 48 ]. Our previous study found that astragaloside IV can increase the expression of HCN4 in injured SANCs of newborn rabbits, protect the damaged cytoskeleton, and improve the survival level of SANCs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS can also damage actin and excitatory-contractile coupling proteins, resulting in cardiac muscle systolic/diastolic dysfunction. Moreover, insufficient ATP synthesis leads to a lack of energy supply to cardiomyocytes, which has serious adverse effects on cardiomyocyte survival and cardiac ejection function [53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, severe diabetic cardiomyopathy with heart failure is accompanied by myocardial hypertrophy, partial myocardial ischemia, and hypoxia [36,53]. The energy metabolism of myocardial cells is converted from fatty acid oxidation to glycolysis to adapt to hypoxia as a selfprotective mechanism.…”
Section: Discussionmentioning
confidence: 99%